Method for manufacturing lithium sulfide

KR103018929B1Active Publication Date: 2026-09-11MITSUBISHI MATERIALS CORP
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
KR1020227031781
Authority / Receiving Office
KR · KR
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-03-17
Filing Date
2021-02-02
Publication Date
2026-09-11
Estimated Expiration
2041-02-02

Smart Images

  • Figure 112022096227116-PCT00002_ABST
    Figure 112022096227116-PCT00002_ABST
Patent Text Reader

Abstract

A method for manufacturing lithium sulfide includes a preparation process (step S12) of introducing a reducing agent and a raw material having a characteristic of losing weight by 5% or more and 25% or less up to 120°C into a furnace, and a heating process (step S14) of heating the raw material and the reducing agent in the furnace to raise the temperature.
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] The present invention relates to a method for manufacturing lithium sulfide. Background Technology

[0002] Lithium sulfide is known as a solid electrolyte for lithium batteries. Patent Document 1 discloses a method of producing lithium sulfide by reacting lithium hydroxide with hydrogen sulfide in a non-protonic organic solvent to form lithium hydrosulfide, and further proceeding the reaction.

[0003] Patent Document 2 discloses a method for manufacturing lithium sulfide without using an organic solvent. In Patent Document 2, lithium sulfide is produced on the lithium metal by reacting metallic lithium with sulfur vapor or hydrogen sulfide. Then, the unreacted lithium metal is melted by heating it to a high temperature, diffused and infiltrated into the already produced lithium sulfide, and then cooled. Then, lithium sulfide is produced again by reacting the lithium metal with sulfur vapor or hydrogen sulfide. This cycle is repeated to react the lithium metal to 100%.

[0004] Patent Document 3 discloses a method for producing lithium sulfide by reacting lithium carbonate with hydrogen sulfide.

[0005] Patent Document 4 discloses a method for manufacturing lithium sulfide without using hydrogen sulfide. In Patent Document 4, lithium sulfate and carbon powder are each adjusted into fine particles and mixed to increase the reaction surface area and reduce unreacted raw materials. Prior art literature

[0006] Japanese Published Patent Application No. 2006-151725, Japanese Published Patent Application No. Hei 9-110404, Japanese Published Patent Application No. 2012-221819, Japanese Published Patent Application No. 2013-227180 The problem to be solved

[0007] In the technology described in Patent Document 1, costs increase because organic solvents are used. In the technology described in Patent Document 2, costs increase because it is necessary to repeat the reaction cycle. In the technology described in Patent Document 3, toxic hydrogen sulfide gas is used, so management is difficult and there is a concern that it may be difficult to ensure safety. In the technology described in Patent Document 4, the process increases because the material must be adjusted and mixed into fine particles. In addition, when manufactured using equipment such as a rotary kiln, there is a concern that the amount recovered may be reduced as fine particles scatter inside the equipment. As such, there is room for improvement in the method for manufacturing lithium sulfide with high ion conductivity used in lithium batteries.

[0008] The present invention is made in consideration of the above and aims to provide a more suitable method for manufacturing lithium sulfide with high ion conductivity. means of solving the problem

[0009] To solve the problem described above and achieve the objective, the method for manufacturing lithium sulfide according to the present invention comprises a preparation process of introducing a raw material having a characteristic of losing weight by 5% or more and 25% or less up to 120°C and a reducing agent into a furnace, and a heating process of heating the raw material and the reducing agent in the furnace to raise the temperature. Effects of the invention

[0010] The method for manufacturing lithium sulfide related to the present invention has the effect of being able to more appropriately manufacture lithium sulfide with high ion conductivity. Brief explanation of the drawing

[0011] Figure 1 is a flowchart showing the process of a method for manufacturing lithium sulfide. FIG. 2 is a schematic diagram showing an example of a manufacturing apparatus including a rotary kiln. Figure 3 is an SEM image of the lithium sulfate raw material when heated in the present embodiment. Figure 4 is a graph showing the test results of an example and a graph showing the measurement results of X-ray dilation measurement. Figure 5 is a graph showing the test results of an example and a graph showing AC impedance measurement. Specific details for implementing the invention

[0012] The present invention will be described in detail below with reference to the drawings. Furthermore, the present invention is not limited by the forms for carrying out the invention described below (hereinafter referred to as embodiments). In addition, the components in the following embodiments include those that can be easily conceived by those skilled in the art, substantially identical ones, and those within the so-called equivalent range. Furthermore, the components disclosed in the following embodiments can be appropriately combined.

[0013] Using FIGS. 1 and 2, a method for manufacturing lithium sulfide is described. FIGS. 1 is a flowchart showing the process of a method for manufacturing lithium sulfide. FIGS. 2 is a schematic diagram showing an example of a manufacturing apparatus including a rotary kiln.

[0014] The method for manufacturing lithium sulfide according to the present embodiment involves placing lithium sulfate as a raw material, which has the characteristic of losing weight by 5% or more and 25% or less up to 120°C, and a reducing agent into one furnace and raising the temperature to produce lithium sulfide.

[0015] A raw material having lithium sulfate as its main component, which has the characteristic of losing weight by 5% or more and 25% or less up to 120°C, is a mixture of lithium sulfate in a hydrated state in which a weight loss of 5% or more and 25% or less occurs among lithium sulfate N hydrate (N = 0 to 1). With such lithium sulfate N hydrate, fine cracks are formed on the surface of the lithium sulfate due to volume changes upon heating, thereby increasing the surface area and reducing unreacted residues. A weight loss of less than 5% is insufficient to induce cracks throughout the entire raw material. Furthermore, in the case of a weight loss of 25% or more, the high moisture content causes particles to bond together, making it difficult to mix with a reducing agent. Additionally, it is inefficient because more moisture than is required to form cracks must be volatilized.

[0016] Lithium sulfate preferably has an average particle size of 10 μm or more and 100 μm or less, more preferably 15 μm or more and 80 μm or less, and even more preferably 30 μm or more and 50 μm or less. The lithium sulfate, which is the raw material for the method of manufacturing lithium sulfide according to the present embodiment, does not need to be in the form of fine particles. For this reason, even when manufacturing using equipment such as a rotary kiln (11), for example, the possibility that the powdered lithium sulfate will scatter inside the kiln body (furnace) (12) of the rotary kiln (11) and become difficult to recover is reduced.

[0017] The reducing agent may be a material having carbon as its main component, such as activated carbon, for example, but is not limited to it. In this embodiment, the case where the reducing agent is activated carbon is described. It is preferable that the activated carbon has an average particle size of 1 μm or more and 10 μm or less.

[0018] As shown in FIG. 1, a method for manufacturing lithium sulfide includes a preparation process (step S12) of introducing lithium sulfate and a reducing agent into a furnace, a heating process (step S14) of heating the furnace, and a cooling process (step S16) of cooling the furnace.

[0019] [Preparation Process]

[0020] In the preparation process, lithium sulfate and a reducing agent are introduced into a furnace in a predetermined molar ratio. Also, in the preparation process, lithium sulfate and a reducing agent are mixed in a predetermined molar ratio. The molar ratio of lithium sulfate to activated carbon, which is the reducing agent, is preferably, for example, a C / Li2SO4 ratio of 2 to 4.

[0021] [Heating Process]

[0022] In the heating process, lithium sulfate and a reducing agent are heated in a furnace to raise the temperature. In the heating process, lithium sulfate is dehydrated and reduced by the reducing agent. In the heating process, for example, under an inert atmosphere with a dew point of -60°C, the temperature is raised to a range of 700°C or higher and 950°C or lower, preferably 800°C or higher and 850°C or lower. The type of inert gas is argon or nitrogen. In the temperature range of 700°C or lower, the reaction rate between lithium sulfate and the reducing agent is slow, resulting in low productivity. In the temperature range of 950°C or higher, lithium sulfide dissolves because it is above the melting point of lithium sulfide. In the temperature range of 850°C or higher, the unreacted lithium sulfate remaining dissolves because it is above the melting point of the raw material, lithium sulfate. In the temperature range of 800°C to 850°C, lithium sulfate does not melt, and lithium sulfide is obtained while maintaining its particulate shape. The temperature range of 800°C to 850°C has a high reaction rate and high productivity.

[0023] In the heating process, it is preferable to increase the temperature at a heating rate of 10 ℃ / min or more after starting heating to reach a desired temperature range. In the heating process, it is preferable that the heating time within the desired temperature range be 5 minutes or more and 90 minutes or less. It is preferable to set the heating time within the above range because if the high temperature is maintained for a long time, grain growth gradually occurs and a decrease in reactivity occurs.

[0024] Figure 3 is an SEM image of the lithium sulfate raw material when heated in the present embodiment. During the heating process, due to the large volume change of the lithium sulfate particles under the conditions of the present embodiment, fine cracks are formed as shown in Figure 3, and the reaction surface area is expanded. As a result, the amount of unreacted lithium sulfate remaining is reduced. Since fine cracks are formed in the lithium sulfate particles, it is not necessary to combine the lithium sulfate into a fine powder form.

[0025] [Cooling Process]

[0026] The cooling process cools the furnace to 200°C or lower after the heating process. The cooling process naturally cools the heated furnace.

[0027] After the cooling process, lithium sulfide is extracted from the furnace.

[0028] The preparation process, the heating process, and the cooling process may be carried out using, for example, a manufacturing device (10) having a rotary kiln (11).

[0029] [Manufacturing device]

[0030] The manufacturing apparatus (10) is a device for producing lithium sulfide by placing lithium sulfate as a raw material and activated carbon as a reducing agent into one furnace and raising the temperature. The manufacturing apparatus (10) includes a rotary kiln (11), a material input device (18), and a discharge pipe (24).

[0031] The rotary kiln (11) includes a kiln body (12), a heater (14), and a driving unit (16). The kiln body (12) is a standard component. It is preferable that the kiln body (12) be positioned with an inclination with respect to the horizontal direction such that the central axis of the cylindrical shape is inclined such that the end facing the material feeding device (18) is vertically higher than the other end. The heater (14) heats the kiln body (12).

[0032] The driving unit (16) rotates the kiln body (12) using a cylindrical central axis as the rotation axis. The driving unit (16) includes a driving source (30) and a transmission mechanism (32). The driving source (30) generates rotational force such as a motor. The transmission mechanism (32) transmits the rotational force of the driving source (30) to the kiln body (12).

[0033] The material input device (18) inputs lithium sulfate and activated carbon into the rotary kiln (11). The material input device (18) includes a material storage section (21) and a supply pipe (22). The material storage section (21) stores lithium sulfate and activated carbon. The supply pipe (22) connects the material storage section (21) and the kiln body (12). The supply pipe (22) is connected to the upstream side of the conveying path of lithium sulfate and activated carbon in the kiln body (12). The supply pipe (22) supplies lithium sulfate and activated carbon from the material storage section (21) to the kiln body (12).

[0034] The discharge pipe (24) is connected to the end opposite to the end to which the supply pipe (22) of the kiln body (12) is connected. The discharge pipe (24) is connected to the downstream side of the conveying path of lithium sulfate and activated carbon in the kiln body (12). The lithium sulfide produced by passing through the kiln body (12) is discharged through the discharge pipe (24).

[0035] In the manufacturing apparatus (10) configured in this manner, first, lithium sulfate and activated carbon in a predetermined molar ratio are introduced from the material input device (18) into the kiln body (12) of the rotary kiln (11). The lithium sulfate and reducing agent introduced into the kiln body (12) are mixed. Then, during the heating process, the kiln body (12) is heated by the heater (14) and rotated around the rotation axis by the driving unit (16). The lithium sulfate and activated carbon supplied to the kiln body (12) move along the conveying path from the supply pipe (22) toward the discharge pipe (24) due to the rotation of the kiln body (12). The lithium sulfate and activated carbon moving along the conveying path are heated to a desired temperature by the heater (14). Since the lithium sulfate and activated carbon are not in the form of fine particles, scattering along the conveying path is suppressed. Then, in the cooling process, the heater (14) is stopped to cool the kiln body (12) and the lithium sulfide. Then, the manufactured lithium sulfide is discharged from the discharge pipe (24) and recovered.

[0036] [Effects of the present embodiment]

[0037] According to the present embodiment, lithium sulfate and a reducing agent can be placed in a single furnace and heated to produce lithium sulfide. In the present embodiment, since it is not necessary to combine the lithium sulfate used as a raw material into fine particles, the increase in the process can be suppressed. When produced in a manufacturing apparatus (10) having a rotary kiln (11), scattering in the return path can be suppressed, thereby preventing a reduction in the amount recovered. Thus, the present embodiment can provide a method suitable for producing lithium sulfide using a manufacturing apparatus (10) having a rotary kiln (11).

[0038] In this embodiment, toxic hydrogen sulfide gas is not used in the manufacturing process. According to this embodiment, the management of the manufacturing process can be facilitated, thereby ensuring safety.

[0039] In this embodiment, costs can be reduced because lithium sulfate and a reducing agent are used in the manufacturing process, and organic solvents are not used.

[0040] Since this embodiment does not require the manufacturing process to be repeated, the time required for manufacturing can be shortened, thereby reducing costs.

[0041] In this way, according to the present embodiment, lithium sulfide can be manufactured more appropriately.

[0042] [Example]

[0043] Next, a method for manufacturing lithium sulfide is described using specific examples. In the preparation process, 0.84 g of lithium sulfate monohydrate, which is the raw material, and 0.19 g of activated carbon, which is the reducing agent, were weighed under an inert atmosphere and mixed in a mortar. The weight loss of the lithium sulfate monohydrate used here upon heating to 120°C is approximately 15%. The mixture of lithium sulfate monohydrate and activated carbon was placed into a crucible formed of aluminum oxide.

[0044] After the preparation process, in the heating process, a crucible containing a mixture of lithium sulfate monohydrate and activated carbon was placed in a small muffle furnace, and the temperature was raised to 850°C over 10 minutes. The temperature was maintained at 850°C for 30 minutes.

[0045] After the heating process was completed, during the cooling process, the inside of the muffler was naturally cooled to recover the sample.

[0046] The prepared sample was ground using an agate mortar and pestle, and then powder X-ray dilution measurements were performed using a D8ADVANCE device manufactured by Burker to evaluate unreacted residues. In addition, 0.3 g of the ground sample was filled into a conductivity measurement cell, and AC impedance measurements were performed at room temperature (25°C) under a pressure of 360 MPa in a measurement range of 1 Hz to 7 MHz.

[0047] In the examples, lithium sulfate monohydrate was used as the raw material. In the examples, activated carbon was used as the reducing agent. In the examples, the molar ratio of carbon to oxygen (C / O2) of the activated carbon was set to 1.2. In the examples, the temperature of the heating process was set to 850 ℃. In Examples 1 to 3, the average particle size of the raw material was varied.

[0048] The average particle size of the raw material lithium sulfate monohydrate was set as "large" for a range of 80 µm or more and 100 µm or less, "medium" for a range of 30 µm or more and 50 µm or less, and "small" for a range of 15 µm or less.

[0049] In the comparative example, anhydrous lithium sulfate was used instead of lithium sulfate monohydrate as the raw material. In the comparative example, the same reducing agent as in the example was used. In Comparative Examples 1 to 5, the average particle size of the raw material and the temperature were varied.

[0050] [Example 1]

[0051] In Example 1, the average particle size of lithium sulfate monohydrate was set to "large". The measurement results of the AC impedance measurement of the sample prepared in Example 1 are shown in Fig. 5.

[0052] [Example 2]

[0053] In Example 2, the average particle size of lithium sulfate monohydrate was set to "medium." The results of the powder X-ray dilation measurement of the sample prepared in Example 2 are shown in Fig. 4. The results of the AC impedance measurement of the sample prepared in Example 2 are shown in Fig. 5.

[0054] [Example 3]

[0055] In Example 3, the average particle size of the lithium sulfate monohydrate was set to "small." The measurement results of the AC impedance measurement of the sample prepared in Example 3 are shown in Fig. 5.

[0056] [Comparative Example 1]

[0057] In Comparative Example 1, the average particle size of the anhydrous lithium sulfate was set to "large." In Comparative Example 1, the temperature during the heating process was set to 850°C. The weight loss of the anhydrous lithium sulfate used in the Comparative Example when heated to 120°C is approximately less than 5%.

[0058] [Comparative Example 2]

[0059] In Comparative Example 2, the average particle size of the anhydrous lithium sulfate was set to "medium." In Comparative Example 2, the temperature during the heating process was set to 850°C. The measurement results of the powder X-ray dilation measurement of the sample prepared in Comparative Example 2 are shown in Fig. 4. The measurement results of the AC impedance measurement of the sample prepared in Comparative Example 2 are shown in Fig. 5.

[0060] [Comparative Example 3]

[0061] In Comparative Example 3, the average particle size of the anhydrous lithium sulfate was set to "small." In Comparative Example 3, the temperature during the heating process was set to 850°C. The measurement results of the AC impedance measurement of the sample prepared in Comparative Example 3 are shown in Fig. 5.

[0062] [Comparative Example 4]

[0063] In Comparative Example 4, the average particle size of the anhydrous lithium sulfate was set to "small." In Comparative Example 4, the temperature during the heating process was set to 750°C.

[0064] [Comparative Example 5]

[0065] In Comparative Example 5, the average particle size of the anhydrous lithium sulfate was set to "small." In Comparative Example 5, the temperature during the heating process was set to 900 ℃.

[0066] The measurement results of the above Examples 1, 2, 3, Comparative Examples 1, 2, 3, 4, and 5 are shown in Table 1 below.

[0067]

[0068] Figure 4 is a graph showing the test results of the examples and a graph showing the measurement results of X-ray dilution measurements. From Table 1, no unreacted residue was observed in Examples 1 to 3. In Example 1, the unreacted residue was in the form of a gray powder. In Examples 2 and 3, the unreacted residue was in the form of a white powder. From Figure 4, it can be seen that in Example 2, only the peak of lithium sulfide appeared, and the peak of the raw material, lithium sulfate, was not observed. The same X-ray dilution measurement results were obtained for Examples 1 and 3 as well. In Comparative Example 1, the unreacted residue contained carbon and became a black powder. In Comparative Example 2, the unreacted residue contained a small amount of carbon and became a gray powder. In Comparative Example 3, no unreacted residue was observed and became a white powder. In Comparative Example 4, the unreacted residue contained carbon and became a black powder. In Comparative Example 5, no unreacted residue is visible, but the sample has melted and formed a mass. Based on these, the Example can reduce unreacted residue compared to the Comparative Example. In the Example, the smaller the average particle size of the lithium sulfate monohydrate, the more the unreacted residue can be reduced. Comparative Example 3 yields results equivalent to the Example, but requires a process of refining the raw material. From this test, it was confirmed that when lithium sulfate monohydrate is used as a raw material, unreacted residue is reduced, and lithium sulfide can be produced more appropriately.

[0069] Figure 5 is a graph showing the test results of the examples and a graph showing the AC impedance measurement. From Figure 5 and Table 1, the AC impedance in Examples 1 to 3 is small. In Comparative Examples 2 and 3, because there is a small amount of carbon or no carbon remains, the AC impedance can be measured, but it is inferior to that of Examples 1 to 3. In Comparative Examples 1 and 4, because carbon remains, it is short-circuited, making it impossible to measure the AC impedance. In Comparative Example 5, the molten sample adheres to the crucible and cannot be recovered with small-scale processing. Based on these, the examples can achieve a higher ionic conductivity than the comparative examples. In the examples, the smaller the average particle size of the lithium sulfate monohydrate, the higher the ionic conductivity can be. From this test, it was confirmed that when lithium sulfate monohydrate is used as a raw material, lithium sulfide with high ionic conductivity can be produced more appropriately.

[0070] From the above, in a method for manufacturing lithium sulfide, by using lithium sulfate monohydrate in which the average particle size of the lithium sulfate monohydrate falls within the range of "medium" or "small," lithium sulfate with low unreacted residue and high ionic conductivity is obtained. From the above, it can be seen that by carrying out the manufacturing under the conditions described above, lithium sulfate having a desired ionic conductivity can be appropriately manufactured. Explanation of the symbols

[0071] 10: Manufacturing device 11: Rotary Kiln 12 : Kiln main body (no) 14 : Heater 16 : Drive unit 18: Material Input Device 21 : Material reservoir 22 : Supply pipe

Claims

Claim 1 A method for producing lithium sulfide, comprising a preparation process of introducing a reducing agent into a furnace, wherein the raw material is lithium sulfate hydrate having a characteristic of losing weight by 5% or more and 25% or less up to 120°C, and a heating process of heating the raw material and the reducing agent in the furnace to raise the temperature, wherein the reducing agent is carbon, and the molar ratio of the raw material and the reducing agent introduced into the furnace is 2 or more and 4 or less as a C / Li2SO4 ratio, and in the heating process, heating to 800°C or more and 850°C or less under an inert atmosphere with a dew point of -60°C to produce lithium sulfide in which the raw material is not melted and maintains its particle shape. Claim 2 A method for manufacturing lithium sulfide according to claim 1, wherein in the heating process, the mixed raw material and the reducing agent are heated. Claim 3 delete Claim 4 A method for manufacturing lithium sulfide according to claim 1 or 2, wherein the heating process has a heating rate of 10 ℃ / min or more.

Citation Information

Patent Citations

  • Method for producing lithium sulfide

    JP2014201510A

  • Manufacturing method of lithium sulfide and manufacturing method of inorganic solid electrolyte

    JP2016216312A